Intellectual Property Protection for Graphical User Interfaces - Mohammad Mahdi Kateb Damghani; Bagher Ansari (پژوهشهای حقوقی)
A graphical user interface is a fundamental part of any software application as it enables users to interact with an application’s functionality, allowing interaction between computer software and hardware. The hybrid nature is a feature of GUIs. Therefore, it can qualify for all three forms of intellectual property protection: patent, copyright, and trademark. Each of these three forms has its pros and cons in terms of protecting graphical user interfaces. However, industrial design rights eventually seem to be the best system for protecting graphical user interfaces. Therefore, this study mainly focuses on the industrial design protection for the GUIs as well as the industrial design protection of GUIs in WTO member states, and in some cases, a comparison has been made with the Iranian legal system. A review of different legal systems indicates that in cases where the user interface is to be supported in more than one country, and at the international level, some points such as the scope of protection, filing routes and priority rights should be considered, and suggestions have been presented for modification of the protection system of GUIs as well as synchronization of protections. Furthermore, there are legal issues with respect to cloud computing and graphical user interfaces that need to be considered, including the protection of the intellectual property of both the user and the provider.